MYC competes with MiT/TFE in regulating lysosomal biogenesis and autophagy through an epigenetic rheostat - Ida Annunziata (Nature Portfolio, 2019)
Genes related to lysosomal and autophagic systems are transcriptionally regulated by the Mit/TFE family of transcription factors. Here the authors show that MYC, in association with HDACs, suppresses the expression of lysosomal and autophagy genes by competing with the Mit/TFE transcription factors for occupancy of their target gene promoters.